2006
DOI: 10.1097/01.mol.0000217890.54875.13
|View full text |Cite
|
Sign up to set email alerts
|

Familial combined hyperlipidemia: upstream transcription factor 1 and beyond

Abstract: Currently, genetic and functional evidence is supportive of a role for upstream transcription factor 1 in the etiology of familial combined hyperlipidemia and its component traits, although the mechanism of causality still remains largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 78 publications
2
31
0
Order By: Relevance
“…7 In many of these studies, there is evidence of sex specificity, with the common allele of rs3737787 showing strongest evidence for association with high TGs in males. 2,3,7 Interestingly, in females, the minor allele seems to be associated with elevated lipids, as well as cardiovascular disease and mortality. 7 The underlying functional mechanisms explaining this replicated sex specificity are currently unknown.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…7 In many of these studies, there is evidence of sex specificity, with the common allele of rs3737787 showing strongest evidence for association with high TGs in males. 2,3,7 Interestingly, in females, the minor allele seems to be associated with elevated lipids, as well as cardiovascular disease and mortality. 7 The underlying functional mechanisms explaining this replicated sex specificity are currently unknown.…”
mentioning
confidence: 99%
“…1 Importantly, FCHL is observed in up to 20% of premature coronary artery disease (CAD) patients. 2 In addition to high serum total cholesterol (TC) and triglycerides (TGs), low plasma levels of high-density lipoprotein cholesterol (HDL-C), small dense low-density lipoprotein particles, and elevated apolipoprotein B (apoB) are also often observed in FCHL. 1,2 Association between FCHL and variants of the upstream transcription factor 1 (USF1) located in the FCHL-linked chromosome 1q21 region was originally identified by Pajukanta et al in Finnish FCHL families.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Our clusters show an average correlation coefficient of 0.85, comfortably over the limit. In the transcription factor dataset which they based these conclusions off of, 22 they found that only 37% of the genes actually showed significant experimental binding to transcription factors. So while with a .85 correlation in the signal suggests only a 50% commonality between two genes, we believe that biologically the percentage in mammalian systems is quite higher due to the relatively sparse nature of the isolated yeast transcription factors.…”
Section: Resultsmentioning
confidence: 99%